MIR-320a/b inhibits cell viability and cell cycle progression by targeting aryl hydrocarbon receptor nuclear translocator-like in acute promyelocyte leukaemia - Hu, Dan; Shen, Zhenji; Yuan, Lin (Polish Journal of Pathology, 2022)
Acute promyelocyte leukaemia (APL) is a subgroup of acute myeloid leukaemia. Dysregulation of clock genes has been revealed to be involved in APL progression. Herein, the mechanism of clock gene aryl hydrocarbon receptor nuclear translocator- like (ARNTL) in APL was explored. The expression of ARNTL, period circadian regulator 1 and 2 (PER1 and PER2) in APL tissue samples and normal samples was analysed by bioinformatic analysis. Gene expression in APL cells was detected by reverse transcription quantitative polymerase chain reaction. Acute promyelocyte leukaemia cell viability and cell cycle progression were assessed by cell counting kit 8 (CCK-8) assays and flow cytometry analyses, respectively. The protein levels of ARNTL and cell cycle markers were examined by western blotting. Interaction between ARNTL and miR-320a/b was confirmed by luciferase reporter assays. Aryl hydrocarbon receptor nuclear translocator-like was overexpressed in marrow tissues of patients with acute myeloid leukaemia and predicted poor outcome. Aryl hydrocarbon receptor nuclear translocator-like knockdown inhibited APL cell viability and arrested APL cells in the G1 phase. Mechanically, ARNTL was targeted by miR-320a/b. Moreover, miR-320a/b upregulation promoted cell cycle arrest in the G1 phase and suppressed the viability of APL cells, and the impacts were reversed by ARNTL overexpression. In conclusion, miR-320a/b suppresses cell viability and leads to cell cycle arrest by suppressing ARNTL in APL.